Analysis of Pectin and Essential Oil Citrus L. Lemon Peel - Singh, Narendra Pratap; Paudel, Nabin (Journal of Tikapur Multiple Campus, 2023)
The most well-known group of aromatic flowers is the genus Citrus. One of the most significant fruit crops in the world belongs to this genus and it is widely grown for the market for fresh fruit and processed juice. The phytochemicals were analyzed in the lemon peel essential oil extract. Phenols, terpenoids, saponins, and alkaloids were analyzed in the acetone extract whereas flavonoids, phenols, and saponins were analyzed in the ethanol extract of Lemon peel. The Fusarium was inoculatedin Petridis and sprayed essential oil over the Petridis. One Petridis was free from essential oil. The essential oil free Petridis was observed spreading fungus with multiplication but the growth of fungus was stopped in Petridis which was sprayed with essential oil after three weeks. The pectin was extractedfrom lemon peel and calculated equivalent weight of pectin was 200g. It is found that lemon peel has a big application in medicinal and pharmacological benefits. Pinontoan et al., 2019 reported that essential oil extract of Lemon peel have equal effectiveness against both Trichophyton rubrum and Fusarium. The family Rutaceae is dominated economically by the genus Citrus L.